Relationship between physical performance and mild cognitive impairment in elderly hemodialysis patients is modified by the presence of diabetes: A multicenter cross-sectional study - Zhao, Yinjiao; Song, Peiyu; Zhu, Chan; Zhang, Lingyun; Chen, Xiaoyu; Zhang, Hui; Han, Peipei; Ding, Wei; Niu, Jianying; Zhao, Junli; Shao, Xiang; Zhang, Liming; et al. (Frontiers in Endocrinology, 2022)
31 Objective: The purpose of this study was to observe the relationship between physical performance 32 and mild cognitive impairment (MCI) in the presence or absence of type 2 diabetes in elderly 33 hemodialysis patients. 34 Methods: In this multicenter cross-sectional study, 396 clinically stable and aged ≥60 years old 35 hemodialysis patients (male 255; mean age: 68.3±5.9 years) were included from 7 dialysis units in 36 Shanghai, China. The Chinese version of the Modified Mini-Mental State Examination (MMSE) and 37 the Instrumental Activities of Daily Living (IADL) scale were utilized to assess MCI. The 38 performance-based assessments consisted of three physical tests: grip strength (GS), Timed Up and Go 39 test (TUGT) and 4-meter walking test, which respectively represent muscle strength, mobility and 40 walking speed (WS). Logistic and multivariate linear regression were used to analysis. 41 Results: Hemodialysis patients with diabetes had high prevalence of MCI (20.6%). In diabetes patients, 42 TUGT and WS were associated with MCI, and WS was negatively correlated with MCI after adjusting 43 covariates [odds ratio (OR)=0.126; 95% confidence interval (CI)=0.023–0.699, P=0.018]. However, 44 no significant association between GS and MCI either in the non-diabetes or diabetes (P>0.05). Further 45 analysis showed that mobility was associated with attention and calculation, and language. Walking 46 speed was related to recall and language in diabetic hemodialysis patients. 47 Conclusions: Physical performance was associated with MCI in diabetic hemodialysis patients rather 48 than the non-diabetes group. Whether increasing mobility or walking speed can positively influence 49 MCI in individuals with type 2 diabetes requires further study.